Water, food and development: the CGIAR Challenge Program on Water and Food - Woolley, Jonathan N.; Cook, Simon E.; David, S.; Harrington, Larry W. (Informa UK Limited, 2009)
Providing the water needed to produce food for more than 9 billion people by 2050 seems simple: agriculture must produce more food with less water. However, three complex issues are involved: First, water, food production and rural development do not have a simple correlation. Second, there are interactions between processes at local, basin and global scales. Third, change involves people in complex networks of institutions. The Challenge Program on Water and Food brings together agriculturalists, hydrologists and development specialists in a global-to-local programme that focuses on change through institutions. We believe that this scale, complexity and involvement are necessary to deliver plausible change.